Isolated supra-cardiac partial anomalous pulmonary venous connection causing right heart failure. Issue 2 (1st January 2016) - Sogomonian, Robert; Alkhawam, Hassan; Zaiem, Feras; Vyas, Neil; Jolly, JoshPaul; Nguyen, James; Haftevani, Emma A. Moradoghli; Dijanic, Christopher; Lieber, Joseph J.
Abstract : Right heart failure (RHF) has been overlooked as left heart failure has predominated. One of the many causes of RHF is partial anomalous pulmonary venous connection (PAPVC), an extremely rare entity in nature. Physicians should consider the unusual causes of RHF after ruling out the common causes.